An empirical study on the effect of outdoor illumination and exercise intervention on Children’s vision - Liao, Shuaixiong; Li, Xueying; Bai, Nan; Wu, Danping; Yang, Wenliang; Wang, Feng; Ji, Hao Zong (Frontiers in Public Health, 2023)
Objective To explore the relationship between outdoor lighting and sports and the development of myopia, and to analyze the effects of outdoor lighting and exercise on the diopter of children with normal vision and myopia, so as to provide guidance for the prevention and treatment of myopia in children and adolescents in the future. Methods A total of 201 children were divided into two groups according to myopia or not. Each group was randomly divided into 4 groups: outdoor exercise group, outdoor control group, indoor exercise group and indoor control group. Among them, the outdoor exercise group and indoor exercise group received moderate and high intensity aerobic exercise 3 times a week for 60 min each time for 12 months, while the outdoor control group and indoor control group had normal study and life during the corresponding period of time. No additional exercise intervention. At the end of the experiment, the diopter of each group was compared. Results The diopter of all groups with normal vision and myopia decreased significantly after the experiment (p < 0.01). There were significant differences in diopter between outdoor exercise group and indoor control group (p < 0.01), between outdoor exercise group and indoor control group (p < 0.05), and between indoor exercise group and indoor control group (p < 0.01). There were significant differences in diopter between indoor exercise group and indoor control group (p < 0.01). The differences among myopic children after the experiment showed that there was significant difference in diopter between outdoor exercise group and indoor exercise group (p < 0.05), between outdoor exercise group and indoor control group (p < 0.01), and between outdoor control group and indoor control group (p < 0.05). There were significant differences in the changes of diopter between the outdoor control group and the indoor exercise group with normal vision and myopia before and after the experiment (p < 0.05). Conclusion Outdoor light and exercise intervention can have a beneficial effect on children’s vision, but because of whether children are myopic or not, the effect is different, outdoor light and exercise have a better effect on reducing the diopter of children with normal vision.